INOVASI PEMBELAJARAN PENDIDIKAN AGAMA HINDU MELALUI METODE DASA DHARMA - Ni Wayan Arsini; I Made Rajendra; Ni Made Ayu Dwi Oktaviani (Padma Sari: Jurnal Ilmu Pendidikan, 2023)
This study aims to conduct a critical analysis related to innovative learning methods that can be applied in learning Hindu Religious Education. Hindu Religious Education is a subject that must be given to Hindu students at all levels wherever they are which has been regulated in the constitution. The role of the Hindu Religious Education teacher is necessary in order to convey a complete understanding of Hindu Religious Education to students, and teachers need learning methods in the process. The dasa dharma learning method, with four new methods namely dharma carita, dharma lila, dharma kriya and dharma brata can be an innovation made by teachers in learning. This research is a qualitative research with a literature study approach, meaning that the data obtained are secondary sources from articles, journals or books which are then analyzed by data reduction, data presentation and conclusions. The results of this study are that the application of the dasa dharma method will greatly assist teachers in inculcating Hindu Religious Education material which generally consists of tattwa, susila, dan upacara. The dharma carita method can be used in providing material related to the cultivation of ethics/susila such as itihasa/purana stories. Meanwhile, with the dharma lila method, material related to tattwa can be provided, such as an understanding of the panca sradhas with the game of snakes and ladders of belief. The dharma kriya method can be used in materials related to upacara such as training in making ceremonial tools, then the dharma brata method to practice self-control and grow spiritual intelligence in students